Ecosystem Protection through Myco-Remediation of Chromium and Arsenic - Neel Kamal; Jagdish Parshad; Baljeet Singh Saharan; Monika Kayasth; Vishal Mudgal; Joginder Singh Duhan; Balwan Singh Mandal; Pardeep Kumar Sadh (MDPI AG, 2023)
The current study emphasizes fungi as an important tool against heavy metals and how isolated fungal species can be used to create a successful strategy for the bioremediation of chromium and arsenic-contaminated sites/soils. Globally, heavy metal pollution is a serious issue. In the current investigation, contaminated sites were chosen, and samples could be taken from various localities of Hisar (29.1492° N, 75.7217° E) and Panipat (29.3909° N, 76.9635° E), India. A total of 19 fungal isolates were obtained from the collected samples through the enrichment culture technique using PDA media supplemented with Cr as chromic chloride hexahydrate (50 mg/L) and As as sodium arsenate (10 mg/L) and the potential of fungal isolates to be used for the removal of heavy metals was examined. The isolates were screened for minimum inhibitory concentrations (MIC) exhibiting tolerance capabilities, and the four best isolates C1, C3, A2, and A6 with the highest MICs (>5000 mg/L), were chosen for further investigations. To use the chosen isolates in the remediation of heavy metals (Cr and As), the culture conditions were optimized. The fungal isolates C1 and C3 estimated the highest removal of 58.60% and 57.00% at 50 mg/L chromium concentration, while the isolates A6 and A2 recorded the highest removal efficiency of 80% and 56% at 10 mg/L arsenic concentration under optimal conditions. Finally, the chosen fungal isolates C1 and A6 were molecularly identified as Aspergillus tamarii and Aspergillus ustus, respectively.